Pumpkin Soygurt Improves Blood Glucose Homeostasis in Diabetes Mellitus Rats Model - Avelia, Annisa; Tamtomo, Didik Gunawan; Sari, Yulia (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
The study aimed to analyze the effect of pumpkin yogurt on insulin resistance in a rat model. The experiment employed 30 male Wistar rats divided into six groups: three control groups (healthy, negative, and positive) and three treatment groups (metformin+PS 1 mL, 1.5 mL, 2 mL). The experiments were conducted for four weeks. Blood glucose homeostasis was measured by fasting blood glucose, insulin, Homeostatic Model Assessment for Insulin Resistance (HOMA-IR), and Quantitative Insulin-Sensitivity Check Index (QUICKI). Administrating a combination of metformin and pumpkin soygurt can control blood glucose homeostasis with an effective dose of 1 mL. Further research should be done on the hormone incretin, which plays a role in insulin secretion.